Modification of the head proteome of nurse honeybees (Apis mellifera) exposed to field-relevant doses of pesticides - Zaluski, Rodrigo; Bittarello, Alis Correia [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira [UNESP]; Padilha, Pedro de Magalhaes [UNESP]; Fernandes, Mileni da Silva; Bovi, Thaís de Souza [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Springer Nature, 2020)
Understanding the effect of pesticides on the survival of honeybee colonies is important because these pollinators are reportedly declining globally. In the present study, we examined the changes in the head proteome of nurse honeybees exposed to individual and combined pesticides (the fungicide pyraclostrobin and the insecticide fipronil) at field-relevant doses (850 and 2.5 ppb, respectively). The head proteomes of bees exposed to pesticides were compared with those of bees that were not exposed, and proteins with differences in expression were identified by mass spectrometry. The exposure of nurse bees to pesticides reduced the expression of four of the major royal jelly proteins (MRJP1, MRJP2, MRJP4, and MRJP5) and also several proteins associated with carbohydrate metabolism and energy synthesis, the antioxidant system, detoxification, biosynthesis, amino acid metabolism, transcription and translation, protein folding and binding, olfaction, and learning and memory. Overall, when pyraclostrobin and fipronil were combined, the changes in protein expression were exacerbated. Our results demonstrate that vital proteins and metabolic processes are impaired in nurse honeybees exposed to pesticides in doses close to those experienced by these insects in the field, increasing their susceptibility to stressors and affecting the nutrition and maintenance of both managed and natural colonies.